초고층 건설공사 시공단계 리스크 요인 도출 및 분석 - 김수용; 김성현; 양진국; Kim, Sooyong; Kim, Sunghyun; Yang, Jinkook (한국건설관리학회 논문집, 17(2), 2016)
High-rise buildings construction project have various risk factors. Major risk factors are negative results such as time delay and increase of costs. Therefore, this study was analyzed risk factors in construction stages of high-rise buildings using by PROMETHEE technique. For this, this research were identified risk factors through experts Focus Group Interview(FGI). And, PROMETHEE was used to setup evaluation standard for analysis of high-rise building construction risks. Next, the standard of evaluation index calculation was composed by using the definition level in PDRI. Preference function and evaluation index were identified through questionnaires. Through these processes, this study has calculated the importance of high-rise building construction risks using by PROMETHEE technique. As a result, high degree risk factors were as following. These are 'Operation plan of material lifting', 'Outrigger & Belt Truss Construction', 'Foundation work plan of high-rise building' and 'Considering a Structure concept of high-rise building'. 고층 건설 프로젝트는 다양한 위험 요인이 있다. 주요 위험 요인은 시간 지연과 비용의 증가 등의 부정적인 결과이다. 따라서, 본 연구는 PROMETHEE 기법을 사용하여 초고층 건설공사 시공 단계에서의 위험 요인을 분석하였다. 이를 위해, 본 연구는 전문가 표적집단면접법(FGI)을 통해 위험 인자를 확인 하였다. 그리고 PROMETHEE는 초고층 건설공사 위험 분석을 위한 설정 평가기준으로 사용 하였다. 다음으로, 평가지표 계산의 기준은 PDRI에서 정의 레벨을 사용하여 구성하였다. 선호지수 및 평가 지표는 설문을 통해 규명되었다. 이러한 과정을 통해, PROMETHEE 기법을 이용하여 본 연구는 초고층 건설공사 시공 리스크의 중요도를 산정하였다. 그 결과, 높은 수준의 위험 요인은 다음과 같이 나타났다. 이것은 '재료 리프팅 운영 계획', '아웃리거 벨트 트러스 건설', '고층 건물의 기초 작업 계획'과 '고층 건물의 구조 개념을 고려'이다.